Elections and electoral system - Tunku Mohd Mokhtar, Tunku Mohar (Cengage Learning, 2008)
Malaysia operates a parliamentary democracy in which elections play an important role,l Since independence in 1957, Malaysia has held elections at regular intervals. Except for an ethnic riot between the Malays and the Chinese following general elections in 1969 (which suspended parliamentary democracy for about two years), elections were held relatively peacefully,